Book Review: Menuju Dialog Teologis Kristen Islam - Arthur Aritonang (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
Dr. Bambang Noorsena wrote this book containing a collection of articles and various independent works by Noorsena, which have been presented numerous times since the end of 1997. These writings are framed under a title: Towards Christian-Islamic Theological Dialogue. This article is motivated by the burden of history, where in the Indonesian context, the carriers of religions such as Islam are identified with Arabs (Middle East). At the same time, Christianity is synonymous with the West. According to Noorsena, Christianity in Indonesia has been uprooted from its Middle Eastern roots due to Westernization. Thus this research aims to bridge the gap between Islam and Christianity in the theological dialogue Noorsena offers a discourse on Middle Eastern Christianity (Syrian Christianity) in Indonesia. Traditionally/the Islamic model preserves the traditions/models of worship of Syriac Christianity and Judaism.